Optimization of PCR protocols for microsatellite primer for slipper-shaped osyter (Crassostrea iredalei) from Brgy. Pinamuc-an, New Washington, Aklan - Respicio, Ramon Lorenz J.
The improvements on culture of slipper-shaped oyster, Crassostrea iredalei are hindered due to the lack of genetic profiles of populations that are basis for selective breeding. To generate genetic profiles of the oyster populations, optimal PCR conditions of microsatellite primers have to be determined. In this study the PCR conditions specifically annealing temperature of microsatellite primers of CI.A11, CI.B07, CI.C09 and CI.D12 were determined by placing the samples under a gradient annealing temperature with PCR other conditions following a standard. Primer CI.A11 was found to amplify a 631.6bp and 223.2bp allele at an annealing temperature of 53.4°C. Primer CI.B07 was able to amplify a 127.7bp and a probable 664.5bp allele at an annealing temperature of 59.2°C. Primer CI.C09 was able to amplify a 180.1bp homozygous allele at an annealing temperature of 58.0°C. Primer CI.D12 only showed probable amplification at annealing temperatures below 45.9°C and was discarded as low annealing temperatures lead to nonspecific primer annealing to the template DNA.